EVALUASI BEBAN KERJA MENGGUNAKAN METODE FULL TIME EQUIVALENT DAN WORKLOAD INDICATORS OF STAFFING NEED DENGAN USULAN PERBAIKAN BERDASARKAN FISHBONE DIAGRAM DI INSTALASI FARMASI RSUD JARAGA SASAMEH - Kristi Melsi; Wiwin Herdwiani; Ika Purwidyaningrum (As-Syifaa Jurnal Farmasi, 2026)
The high volume of services in hospital pharmacy installations is often not matched by the availability of adequate human resources, resulting in an imbalance in workload that affects service quality. This study aims to analyze pharmaceutical staffing needs based on actual workload using quantitative and qualitative approaches, and to identify the causes of excessive workload as a basis for developing recommendations for improving the work system. This study employed a mixed-methods approach with a descriptive, non-experimental observational design and a cross-sectional approach. Quantitative data were collected through direct observation using the work sampling method, as well as the calculation of Full-Time Equivalent (FTE) and Workload Indicators of Staffing Need (WISN). Qualitative data were obtained through in-depth interviews and Focus Group Discussions (FGDs), then analyzed using NVivo and a fishbone diagram. A total sampling technique was applied, involving the entire population of pharmacists and pharmacy technicians (TTK) in the Pharmacy Installation. Data analysis was conducted to determine workforce gaps, as well as barriers and root causes of workload. The results of the study show that the FTE analysis indicates that the overall workload is below capacity with some points of overload. The heaviest workload is in direct patient care. The WISN analysis shows the staffing requirement with a ratio value of 1.10, which means >1 indicates that the workforce is more than sufficient to meet the workload. Therefore, it is concluded that the FTE and WISN methods provide a consistent picture of pharmaceutical labor requirements and can be used in human resource planning in hospital pharmacy installations